Hogar de paso para el mono caquetense y alertas para deforestaciones tempranas (2022)
Designing a temporary home for wild flora and fauna with the appropriate physical-spatial parameters indicates taking into account objectives such as identifying what types of spaces make it up, in this case 3 very important areas are proposed for the primate, such as the an isolation area for a reproduction of the same, an observatory area and some animal care and rehabilitation areas with slightly more private characteristics, additionally other objectives are proposed such as implementing sustainable systems through vernacular materials, that is, those typical of the area, for the which ancestral techniques of the interwoven palm very common in the Amazon were used and which provides an envelope capacity in the facades that manages to sift solar radiation and make animal spaces a more welcoming space with their behavior, as well as establishing the construction of the project mostly with btc wall, construction on land for the land, generating Thus, the least impact on the environment and on the landscape, another objective set is to implement spaces for primates through these landscape elements, for which a system of open-air islands was proposed, with trees, paths around them and a system of water mirrors allowing that the species do not mix, all this contributes to a mimicry with the landscape, embedded in the great challenge of affecting nature as little as possible.